Empowerment of Coastal Communities through the Development of a Sustainable Sea Fish Processing System in the Bohowo Environment, Tongkaina Village, Bunaken District, Manado City, North Sulawesi Province - Talitha Wenifrida Massenga; Dian Sudiantini (CV. Era Digital Nusantara, 2026)
This community empowerment program aims to enhance the economic independence and welfare of the coastal community in the Bohowo area, Tongkaina Village, by developing a sustainable and hygienic sea fish processing system. The main issues identified include the low quality of processed fish products due to the use of traditional methods, limited market access, and the lack of knowledge and technology for hygienic and value-added processing. The program employs a participatory approach through training, mentoring, and the implementation of appropriate technology in fish processing. Activities include training in good handling and processing practices (GHP), the introduction of simple processing technologies (such as smoking and drying with improved equipment), product diversification, and business management. The results of the program show a significant increase in the quality and shelf life of processed fish products, the creation of new product variants with higher economic value, and the establishment of a local business group that manages production and marketing collectively. Furthermore, this program strengthens social capital and environmental awareness within the community through the application of environmentally friendly processing principles and sustainable resource management. This initiative serves as a model for sustainable and empowering community-based economic development in other coastal areas.